ANALISIS KERUSAKAN POMPA HYDRANT DI PLTD LABUHAN SUMBAWA MENGGUNAKAN DIAGRAM FISBHONE - Silvia Firda Utami; Ismi Mashabai; Rapni Yepeikene (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2023)
T. PLN (Persero) UPK Tambora ULPLTD Labuhan is an electricity company that uses diesel engines as prime movers, where prime movers are equipment that functions to produce mechanical energy to rotate generators. PLTD Labuhan was built in 1977 on a 1.2 hectare land on Jalan Labuhan, Garuda, Sumbawa. When founded, it had a central building, subsidiary offices and the official residence of the PLTD head. At that time, there were only two SPD (diesel generators) for this machine, namely SWD DRO 218 K (536 KW) and SWD DRO 216 (336 KW). In this study using the Fisbhone Diagram method. Determination of problems with damage to the hydrant pump using the 4 M + 1 E technique, namely Method, Material, Man, Machine and Environment. The Daigram Fisbhone approach technique produces improvement solutions from the five factors in the Fisbhone Diagram. The Fisbhone Diagram method with the 4 M + 1 E technique allows it to be applied to PT. PLN (Persero) UPK Tambora to minimize damage to the hydrant pump. But still making adjustments related to response time, when it is possible for a fire to occur in companies and buildings, a system is needed that is implemented in a state of alert, so that these companies and buildings can be said to have different functions.